PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Hany Afifah Sausan; Irwansyah Irwansyah; Bramantika Oktavianti (AKUNTABEL, 2015)
The aim of this research is to test and analyze the effect of corporate social responsibility  and  good  corporate  governance  towards  the  firm's  value,  and  to  test profitability in moderating the effect of corporate social responsibility disclosure and good corporate governance towards the firm's value. The research method used is multiple linear regression method for the first model and absolute residual value test for the second model with moderating variabel. Classical assumption test in this research consists of normality test, multicollinearity test, heteroscedasticity test, and autocorellacy test. The result of this research shows that corporate social responsibility effects the firm's  value  insignificantly and good corporate governance negatively  effects the firm's value whilst profitability is not a moderating variable in the connection between corporate social responsibility and good corporate governance with firm's value. It is caused by some factors including investor’s consideration before doing some investment in the go publiccompanies which is various and doesn’t consider the corporate social responsibility or good corporate governance from the company. Key Words        :   Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), Firm's Value, Profitability.